PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS CONTEXTUAL TEACHING AND LEARNING SETTING COOPERATIVE LEARNINGTIPE JIGSAWSUB POKOKBAHASAN BELAH KETUPAT DAN LAYANG-LAYANG KELAS VII SMP - Gunariyanto, Eko; Trapsilasiwi, Dinawati; Kristiana, Arika Indah (KadikmA, 2014)
Abstract.The research purpose is to know the process and result of development of mathematics learning instruments based on contextual teaching and learning by setting of cooperative learning jigsaw for rhombus and kitestopic at seventh grade of junior high school. The products refer to the component of contextual teaching and learningand phases of jigsaw. Learning instrumentsdevelopment model refers to 4D Thiagarajanmodels which has 4 steps namely define, design, develop, and disseminate.This research has fourproducts namely lesson plan, worksheet,student book and evaluation test. Based on the validation process and try out of learning sets can be concluded that the learning sets have satisfied of the validity, practice, and effective criteria. The data collection methods used in this research is, test interview, documentation, observation,and questionnaire. Key Words: 4DThiagarajanmodels, contextual teaching and learning, cooperative learning jigsaw, rhombus and kites